Nancy Drew and the Clue Crew : The Cinderella Ballet Mystery - Book 4 - Keene, Carolyn; Pamintuan, Macky (New York : Aladdin Paperbacks, 2008)
When Nancy and her friends are going to be in a ballet version of Cinderella and the special glass slippers go missing, Nancy is determined to find them before show time.
Reprint. Originally published: 2006.
Keywords: Ballet -- Fiction; Lost and found possessions -- Fiction; Fiction; Juvenile fiction